HUBUNGAN ASUPAN SERAT PANGAN DENGAN PERUBAHAN KETEBALAN TUNIKA INTIMA MEDIA KAROTIS PASCASTROKE ISKEMIK - Isnawan Widyayanto,* Dodik Tugasworo,* Dwi Pudjonarko* (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION DIETARY FIBER HAS PROTECTIVE EFFECT AGAINST PROGRESSION OF ATHEROSCLEROSIS THROUGH THE REGULATION OF SERUM LIPID CAROTID INTIMAMEDIA THICKNESS CIMT IS A MARKER OF ATHEROSCLEROSIS AND RELATED WITH STROKE RISK INCIDENCE AND RECURRENT STROKE